La alimentación cotidiana en la Cataluña del siglo XVIII - Pérez Samper, María de los Ángeles (Cuadernos de Historia Moderna, 2009)
History and time have proved that food has always been a matter of vital importance for the human being all around the world. And, besides, it is a basic need that has to be daily satisfied. Although it is the same need for everybody, along history each group has solved the problem in a different way and in each period in history, groups or individuals have covered this unavoidable need within a general frame of its civilization but always according to their means and resources. The responses to this universal and permanent phenomenon have been multiple and varied. Food can be of great significance to study everyday life in any society at any time. As far as we are concerned, food has been used to study from different sources Catalan society in the 18th century. The Barón de Malda’s dietary book known as “Calaix de sastre”, gives us a very rich and expressive personal view of the plentiful and high quality of the food taken by the Catalan nobility. Records of dishes served to Erasmo de Gónima, a bourgeois enriched with the Industrial Revolution, gives us a good account of social promotion through food. Francisco de Zamora’s survey classifies the different types of food according to upper or lower class society as well as urban or rural areas. It has been through the different sources used in our research that we have been able to see the food variety in the Catalan daily life of the Early Modern History.